1987
DOI: 10.1182/blood.v69.6.1605.1605
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and phenotypic characterization of three new human myeloma cell lines (U-1957, U-1958, and U-1996)

Abstract: Three new human myeloma cell lines (U-1957, U-1958, and U-1996) have been established in vitro. The cell lines are Epstein-Barr virus (EBV) negative, monoclonal, and aneuploid and should thus represent malignant cell populations and not EBV-carrying non-neoplastic B lymphoblastoid cell lines. The myeloma origin of the cell lines is also suggested by their capacity for production of monoclonal complete immunoglobulin (Ig) molecules (U-1957 and U-1958) or IgG light chains (U-1996) of the same type as the myeloma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1987
1987
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…The HL407L cell line grows both adherent and in suspension and express both IL‐6 protein and IL‐6 receptors (38). The U‐1958 (39) and U‐266–1970 (22, 40) cell lines grow both adherent and in suspension, and are dependent on IL‐6 for survival and/or growth (23, 37). Therefore, these cell lines are routinely grown on IL‐6 producing AG1523 fibroblasts (The Human Mutant Genetic Cell Repository, Camden, NJ, USA).…”
Section: Cell Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…The HL407L cell line grows both adherent and in suspension and express both IL‐6 protein and IL‐6 receptors (38). The U‐1958 (39) and U‐266–1970 (22, 40) cell lines grow both adherent and in suspension, and are dependent on IL‐6 for survival and/or growth (23, 37). Therefore, these cell lines are routinely grown on IL‐6 producing AG1523 fibroblasts (The Human Mutant Genetic Cell Repository, Camden, NJ, USA).…”
Section: Cell Linesmentioning
confidence: 99%
“…The IL‐6‐dependent MM cell lines U‐266–1970, U‐1958, and HL407L (23, 37, 39) and CD138+ non‐neoplastic plasma cells, isolated from human tonsils, were analysed by flow cytometry for the expression of Bcl‐2, Bcl‐xL/S, Mcl‐1, Bcl‐w, Bak, Bax, and Bad. The specificity of the polyclonal abs was confirmed by Western blot analysis.…”
Section: Expression Of the Bcl‐2 Family Of Proteins In MM And Cd138+ mentioning
confidence: 99%
“…Although autocrine mechanisms of myeloma cell growth have been documented by several authors (16,17), the establishment of spontaneously proliferating myeloma cell lines in vitro is extremely difficult (1). In addition to autocrine mechanisms, paracrine mechanisms have also been suggested to play an important role in myeloma cell growth (1,4,18,19).…”
Section: Discussionmentioning
confidence: 99%
“…Although autocrine mechanisms of myeloma cell growth have been documented by several authors (16,17), the establishment of spontaneously proliferating myeloma cell lines in vitro is extremely difficult (1). In addition to autocrine mechanisms, paracrine mechanisms have also been suggested to play an important role in myeloma cell growth (1,4,18,19). Our results agree with the paracrine mechanisms of myeloma cell growth ; bone marrow-derived myeloma cell lines proliferate in the presence of MOs, MDF is able to substitute for the M(b functions, Mos produce IL-6, myeloma cell lines most strongly proliferate in response to rIL-6, a-IL-6 antibody inhibits the rIL-6or MDFinduced proliferation of myeloma cell lines, and myeloma cell lines have been maintained for >1 yr in the medium containing rIL-6.…”
Section: Discussionmentioning
confidence: 99%
“…Nilsson et al (1970) reported the establishment of a MM cell line, 266Bl later named U‐266, using a skin fibroblast monolayer. Other authors confirmed that fibroblast‐conditioned medium was able to stimulate the growth of human myeloma cells (Jobin et al , 1974; Jernberg et al , 1987). Kawano et al (1988) first showed that human myeloma cells proliferate in response to interleukin (IL)‐6.…”
mentioning
confidence: 83%